EVALUATION OF ORGANIC RICE AGRICULTURE SYSTEM (ORAS) IN THE SEMARANG DISTRICT - Dwi Erlina Estuningtyas; Muniffatul Izzati; Hartuti Purnaweni (Diponegoro University, 2013)
Along with the increasing public awareness of environmental issues, health, and food safety and quality and make awareness of the importance of organic farming in several countries around the world, including in Indonesia is increasing rapidly. This study aims to analyze the program and implementation of organic rice farming system in the District of Semarang. The research was conducted in the District of Semarang District Susukan starting from April 2013 until August 2013. Secondary data used for the analysis and evaluation of organic rice farming program from the data of 5 (five) years. Secondary data were obtained from farmer groups and related agencies such as the Department of Agriculture, Plantation and Forestry, Bappeda, as well as the Agricultural Extension Center. Primary data obtained from direct observations in the field using the questionnaire in the sample set. Primary data from observational observations made in the current year at the sites. Variable / fenomea observed include compatibility between the implementation of organic rice farming in the community with the criteria of organic farming. The results showed that farmers have carried out SPPO with a percentage of 83.3 percent and 16.7 percent SPK. Basically, organic rice cultivation activities in Semarang district actually can not be said to be fully as organic rice farming, or more accurately described as semi-organic farming systems.